Optimal Time Interval for Surgery After Neoadjuvant Chemoradiotherapy in Patients With Locally Advanced Rectal Cancer: Analysis of Health Insurance Review and Assessment Service Data - Min Jung Kim; Jin Suk Cho; Eun Mi Kim; Woo Ah Ko; Jae Hwan Oh (Annals of Coloproctology, 2018)
Purpose Pathologic downstaging of rectal cancer has been suggested to be associated with the time interval from chemoradiotherapy (CRT) completion to surgery. We aimed to evaluate the effect of this time interval for patients with rectal cancer on the pathologic response. Methods All patients with rectal cancer undergoing neoadjuvant CRT with evaluable data were selected from among the Health Insurance Review and Assessment Service data. Patients were divided into groups according to the time between CRT and surgery. CRT responses were analyzed. Results Two hundred forty-nine patients were included, of whom 86 (34.5%) were in the 5- to 7-week interval, 113 (45.4%) in the 7- to 9-week interval, 38 (15.3%) in the 9- to 11-week interval, and 12 (4.8%) in the >11-week interval. The median time interval between CRT completion and surgery was 7.4 weeks (range: 5–22.7 weeks; interquartile range, 6.7–8.7 weeks). Surgery 9–11 weeks after CRT completion resulted in the highest, but not statistically significant, pathologic complete response (pCR) rate (3 patients, 8.6%; P = 0.886), no pCR was noted in the >11-week interval group. Results for downstaging in the 9- to 11-week interval group were as follows: T downstaging, 38.2% (P = 0.735); N downstaging, 50.0% (P = 0.439); and TN downstaging, 52.9% (P = 0.087). The 3-year overall survival rates for the 5- to 7-week, 7- to 9-week, 9- to 11-week, and >11-week interval groups were 93.0%, 85.0%, 81.6%, and 91.7%, respectively (P = 0.326). Conclusion Delaying surgery by 9 to 11 weeks may increase TN downstaging, but delaying for over 11 weeks may not increase additional tumor downstaging from long-course CRT.